Advancing Pharmacy Practice in Tanzania: A Descriptive Report of Pharmacy Education and Practice Models in 3 Institutions. (March 2021) - Mbilinyi, Christian; Buma, Deus; Ngasa, Solobi; Maingu, Rose; Maganda, Betty; Kaali, Wellu; Uledi, Mtoke; Mkinga, Bryceson; Njonjo, Bruno; Amiri, Jumanne; Zuckerman, Autumn D.
Understanding models of pharmacy education and practice in low-to-middle income countries (LMIC) can drive best practices and resource utilization. However, there is a paucity of literature in this setting. The purpose of this report is to describe the length and breadth of pharmacy education and training in Tanzania as well as pharmacy practice models at 3 institutions. Lessons learned and implications for global pharmacy practice described herein aim to advance the profession and pharmacists' impact in LMIC settings. The Muhimbili campus is located in Dar es Salaam, the largest city in Tanzania, a LMIC in East Africa, and is comprised of 3 institutes and a health professions school. Despite variance in patient populations, all Muhimbili institutions have developed pharmacy services in outpatient and inpatient pharmacies, central pharmacy stores, intensive care units, and operating theaters. Unique pharmacy practice areas result from a variance in patient populations serviced and include services in pharmacovigilence/drug information, compounding, oncology, nephrology, and emergency departments. Medication availability and the complexity and time commitment of patient billing are consistent challenges, and multidisciplinary collaboration a common strength across the 3 institutions. Pharmacists at Muhimbili perform innovative and critical functions to support optimal patient care tailored to specific patient populations. The detailed review of these services can serve as a model for pharmacy practice at other health systems in LMIC and beyond.